Quasi-planar substrate integrated waveguide pyramidal horn antenna for Ku-band applications - Ashraf S.A.; Singh S.; Sahu B.; Singh S.P. (My University, 2025)
In this paper, a novel quasi-planar substrate integrated waveguide (SIW) pyramidal horn antenna for Ku-band applications is presented. The proposed antenna provides wider multiple frequency sub-bands in Ku-band and improved E-plane half power beamwidth. Although the proposed design affects the planarity of the antenna to some extent but by and large it maintains the compactness of the antenna. In addition, the proposed horn is easy to fabricate and preserves two most important characteristics of SIW technology, namely compactness and easy manufacturing. Dimension optimization of the antenna and simulation studies of its input and radiation characteristics were performed using Ansys HFSS software. Further, a prototype of the proposed antenna was fabricated on FR4 substrate of dimensions 35 mm × 35 mm × 3.2 mm and antenna characteristics were determined experimentally. It is found that simulated antenna characteristics are nearly in agreement with the corresponding experimental ones, which verify the proposed antenna concept. © 2017 Wiley Periodicals, Inc.